The Influence of Product Quality, Price and Brand Quality on Consumer Satisfaction with Ms Glow Beauty Products - Ariyanto, Ariyanto; Pujiati , Herni (Dinasti International Journal of Management Science, 2025)
This study aims to determine the relationship and influence of Product Quality, Price, and Brand Image on Consumer Satisfaction of MS Glow Beauty Products (Case Study on MS Glow Beauty Consumers in Ayshop Cosmetics Stores) which collected as many as 100 consumers who bought and used MS Glow beauty products at the Ayshop Cosmetics Store. The collected data were analyzed using a validity test & reliability of the data, then a multiple linear analysis check was carried out. The results of the study partially show that product quality, price and brand image have a positive impact and are significant to consumer satisfaction. This result is proven by the t-test for each free variable. The t test results for testing product quality variables were obtained t count 5.068 > t table 1.984 and Sig values ??0.000 < 0.05, so Ho was rejected and Ha was accepted, meaning that product quality had a positive and significant effect on consumer satisfaction. T test results for price variable testing were obtained t calculate 4.401 > t table 1.84 and Sig value 0.000 < 0.05 so that Ho was rejected and Ha was accepted, meaning that the price had a positive and significant effect on consumer satisfaction. The results of the t test for testing the brand image variable were obtained t count 3.842 > t table 1.984, so that Ho was rejected and Ha was accepted, meaning that the brand image had a positive and significant effect on consumer satisfaction. The results of research on product quality, price and brand image together) have a positive and significant effect on consumer satisfaction. This result is proven by the F test, which is obtained F count 50.32 > F table 2.70 and Sig value 0.000< 0.05, so ho is processed and Ha is accepted. This means that product quality, price, brand image together have a positive and significant effect on consumer satisfaction.